The Success Of Exclusive Breast Feeling From The Knowledge Of The Mother And The Role Of Officials Health In Bunder Village Malang In 2020 - Denis Nur Indah Sari; Miftakhur Rohmah (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2023)
The low level of providing exclusive breastfeeding in Bunder Village, Malang, Bunder Village, from a preliminary study that has been conducted from 10 mothers who have babies aged 6 months, only 2 give exclusive breastfeeding.Research Objectives : To analyze the relationship between maternal knowledge and the role of health workers with the success of exclusive breastfeeding in Bunder Malang Village in 2020. This study used an analytic survey method with a cross-sectional approach. Population and sample in this study were all mothers who have babies aged 6-12 months with 30 respondents. The sampling method using non random method with accidental sampling technique. Data collection using a questionnaire. Statistical test using chi square. From the research results, it was found that of the 30 respondents, 21 respondents (70%) had poor knowledge and 9 respondents (30%) had good knowledge. From the Chi-Square test results obtained p value 0.002 <α 0.05, which means that there is a relationship between maternal knowledge and offering exclusive breastfeeding. While the role of health workers from 30 respondents who got a score of ≥75 was 17 people (56.7%) more than those who got a score of <75, namely as many as 13 people (43.3%). From the Chi-Square test results obtained p value 0.017> α 0.05, which means there is a relationship between health workers and offering exclusive breastfeeding. From the whole analysis process that has been carried out, it can be concluded that there is a relationship between maternal knowledge and the role of health workers, with exclusive giving.